Tough on crime: The rhetoric and reality of property crime and feeling safe in Australia - Baker, D (The Australia Institute, 2013)
There is a reality gap between declining crime rates and the popular rhetoric of ‘tough on crime’ media stories and political policies. As the property crime rate has fallen, there has been a corresponding increase in reported feelings of safety. Perceptions of social disorder had the greatest overall influence on people's reported feelings of safety, followed by reported levels of nervousness.
Policy Brief No. 56
Keywords: Stress -- Life events; Life Events -- Crime; Beliefs and Values; Disadvantage, adversity and resilience; Beliefs and Values; Life Events; Stress; Life events; Crime; Dsiadvantage, adversity and resilience; Adversity and resilience